2015
DOI: 10.1039/c4py01753f
|View full text |Cite
|
Sign up to set email alerts
|

Using click chemistry to dial up the modulus of doubly crosslinked microgels through precise control of microgel building block functionalisation

Abstract: ABSTRACT:Doubly crosslinked microgels (DX MGs) are hydrogels constructed by covalently interlinked vinyl-functionalised microgel particles. Until now it has not been possible to precisely control the extent of vinyl functionalisation of the microgel (MG) particles which act as the colloidal building blocks for hydrogel assembly. Furthermore, the range of DX MGs prepared to date has been modest. This study addresses both of these challenges by constructing a new class of DX MG using MG particles that were vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[13][14][15][16] For example, the presence of large-size fractures greater than inches resulted in severe lost circulation and water early breakthrough since such technical challenges posed potential threats to field production. [17][18][19] However, large fractures treatments using traditional granular hydrogels proved to be fruitless due to weak interactions. [20][21][22] Severe lost circulation required granular hydrogels with excellent injectivity, mechanical robustness against destructive forces, and self-regenerative functions to seal the fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] For example, the presence of large-size fractures greater than inches resulted in severe lost circulation and water early breakthrough since such technical challenges posed potential threats to field production. [17][18][19] However, large fractures treatments using traditional granular hydrogels proved to be fruitless due to weak interactions. [20][21][22] Severe lost circulation required granular hydrogels with excellent injectivity, mechanical robustness against destructive forces, and self-regenerative functions to seal the fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The highly stable aromatic structure of triazole has the advantages of being tolerable to acidic, basic, and oxidative mediums, 27 mimicking amide groups and acting as hydrogen bond acceptors to improve mechanical strength. 28,29 Although some research toward improving mechanical properties 30,31 using click chemistry has been reported, application of CuAAC in the crosslinking of waterborne polymers has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Click chemistry, especially copper-catalyzed 1,3-dipolar azide–alkyne cycloaddition (CuAAC), is insensitive to oxygen, water, solvents, and a wide range of functionalities and can be site-specifically performed at room temperature , with high reaction rates and quantitative yields . As one of the most effective chemical reactions, click chemistry has been widely used in the synthesis, modification, and engineering of polymers, to obtain linear or branched polymers, , to conjugate or link small molecules or macromolecules, and to cross-link click-suitable polymers. The highly stable aromatic structure of triazole has the advantages of being tolerable to acidic, basic, and oxidative mediums, mimicking amide groups, and acting as hydrogen bond acceptors to improve mechanical strength. , Although some research toward improving mechanical properties , using click chemistry has been reported, application of CuAAC in the cross-linking of waterborne polymers has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51] However, while being a valuable tool for many coupling reactions, this family of reactions has never been investigated so far in DX microgel formation, except to introduce vinyl functions onto microparticle surfaces as reported recently by Saunders et al In their strategy, copper catalyzed azide-alkyne cycloaddition (CuAAC) was investigated to precisely control the extent of vinyl functionalization of the microgel (MG) particles and therefore dial up the modulus of the resulting DX microgels. 52 Herein, we describe for the first time the use of a metalfree, click coupling reaction to interlink well-defined microparticles. In particular, we are taking advantage of the 1,2,4triazoline-3,5-dione (TAD) based click chemistry, as previously introduced by some of us.…”
Section: Introductionmentioning
confidence: 99%